2016
DOI: 10.3171/2015.6.spine15268
|View full text |Cite
|
Sign up to set email alerts
|

Thoracolumbar kyphoscoliosis with unilateral subluxation of the spine and postoperative lumbar spondylolisthesis in Hunter syndrome

Abstract: Surgical correction for kyphoscoliosis is increasingly being performed for patients with mucopolysaccharidosis (MPS). Reported case series have predominantly included patients with Type I (Hurler) and Type IV (Morquio) MPS. To their knowledge, the authors describe the first case report of surgical management of thoracolumbar kyphoscoliosis in Hunter syndrome (MPS Type II) and the rare occurrence of lumbar spondylolisthesis following surgical stabilization. A 12-year-old boy with Hunter syndrome present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 15 publications
1
5
0
2
Order By: Relevance
“…An asymmetry in the orientation of facet joint surfaces has been previously discussed as a potential cause of spinal degeneration [2,35,42] and instability [1,7,17,21,30,33,53]. This abnormality has been also suggested as an underlying cause of rotatory displacement of the spine in both anteroposterior [47] and axial directions [46].…”
Section: Discussionmentioning
confidence: 95%
“…An asymmetry in the orientation of facet joint surfaces has been previously discussed as a potential cause of spinal degeneration [2,35,42] and instability [1,7,17,21,30,33,53]. This abnormality has been also suggested as an underlying cause of rotatory displacement of the spine in both anteroposterior [47] and axial directions [46].…”
Section: Discussionmentioning
confidence: 95%
“…Thoracolumbar kyphosis is a classic finding in MPS I and has also been reported in MPS II, 38 IV and VI. 10 , 39 - 41 Scoliosis can occur in association with kyphosis or in isolation, but surgery for scoliosis is uncommon in the absence of significant kyphosis.…”
Section: Spinementioning
confidence: 84%
“…A 12-year-old boy with kyphoscoliosis was successfully treated with combined anterior/posterior instrumented arthrodesis. 32 Based on available imaging, the evaluation of 39 patients enrolled in the Hunter Outcome Survey showed that in 87% any spine involvement was detected: almost 80% had thoracic vertebral deformity and 3.4% spinal compression, while 94% had lumbar vertebral deformity and 3% spinal cord compression. Spine fusion or decompression was performed in less than 1% of patients.…”
Section: Kyphoscoliosismentioning
confidence: 99%